The fascinating numbers - Mohd Atan, Kamel Ariffin (Universiti Pertanian Malaysia, 1996)
We see numbers almost everywhere and every day in our lives. Numbers such as telephone numbers, car plate numbers and IC numbers serve to organize our daily activities into some order. Numbers are money-spinners for TNB, Telekom and other business concerns and more recently IWK despite the ignorance of its activities by some quarters. Numbers, especially big ones seem to be the nightmares of politicians and economists although the empty one (zero) is an elusive dram for consumers in this age of concern over the threat of inflation. Numbers are conveniently employed to determine the status of salary increments under the SSB.